Estereotipia de parâmetros temporais e espectrais da vocalização de anúncio de anfíbios amazônicos - Ferreira, Ana Carolina Monteiro (Brasil, 2022)
Characteristics of acoustic signals can be classified from static to dynamic based on their coefficients of variation. In anuran amphibians, the amplitude variation of each characteristic composing an acoustic signal normally increases according to the organizational scale of analysis. Static traits (less variable individually), if they show greater variation between populations, indicate a possible role in pre-mating isolation. Studies suggest that, through mate choice, females can exert stabilizing selection over certain traits that become stereotyped (static), while other selection pressures – or the absence of these – result in more variable (dynamic) traits. In this project, we sought to find the potential of the spectral and temporal acoustic signals of the advertisement call as indicators for discrimination between populations by studying the stereotypy of acoustic signals in the Amazonian litter frogs Allobates tapajos and Allobates sumtuosus at intra-individual, intrapopulation and interpopulation scales. To avoid confusion with intrinsic (body size) and ecological (temperature) parameters, we also tested the influence of these possible co-variates on call traits. As observed in previous studies with congener species, none of the vocalization characteristics of both studied species stood out as a potential discriminator among populations, reinforcing the idea that these, in isolation, do not serve as cues for social recognition or sexual selection. Body size was relevant for acoustic traits in only one of the species, A. sumtuosus. Unlike previous studies with Allobates and anurans in general, temperature had little or no effect on the advertisement call of both species, suggesting that the plasticity of advertisement call traits has little relation to this ecological covariate. The idiosyncrasies detected in the group formed by this and other similar studies make it difficult to detect general patterns and emphasize the importance of standardized investigations involving multiple species to understand the variability and determinants of variation in temporal and spectral acoustic parameters of the sexual signals of different species of anurans.